2007
DOI: 10.1002/chem.200700744
|View full text |Cite
|
Sign up to set email alerts
|

Stable Pentacoordinate Carbocations: Structure and Bonding

Abstract: We report that only elements more electropositive than carbon (Group 13, 14, and Be) form stable symmetrical HnE--CH3--EHn + structures (E=Group 1, 2, 13, or 14 element) with a planar CH3 group symmetrically bonded to two EHn moieties, in analogy with prototypical SN2 transition structures. Analysis of the bonding situation of these pentacoordinate carbon molecules was studied by means of an energy decomposition analysis (EDA) of the interaction energy. This shows that HnE--CH3--EHn + molecules can be viewed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 50 publications
3
25
0
1
Order By: Relevance
“…Theoretical works (Jemmis et al, 1979;Ferná ndez et al, 2007) have shown the stability of penta-coordinated carbenium ions and other cations containing more electropositive elements than carbon (Be and Group 13 and 14 elements) and whose bonding scheme also fits to a (2e, 3c) bond.…”
Section: Introductionmentioning
confidence: 97%
“…Theoretical works (Jemmis et al, 1979;Ferná ndez et al, 2007) have shown the stability of penta-coordinated carbenium ions and other cations containing more electropositive elements than carbon (Be and Group 13 and 14 elements) and whose bonding scheme also fits to a (2e, 3c) bond.…”
Section: Introductionmentioning
confidence: 97%
“…It is worth mentioning that inspired in this study showing the stabilization of the Si 2 (CH 3 ) 7 + ion through the contribution of threecenter-two-electron bonds, it was predicted, on theoretical grounds, that a similar stabilization occurs for the Ge, Sn and Pb containing analogues [71]. Based on the fact that the structure predicted for the Si 2 (CH 3 ) 7 + ion in ref.…”
Section: Pentacovalent Carbon Atomsmentioning
confidence: 65%
“…Based on the fact that the structure predicted for the Si 2 (CH 3 ) 7 + ion in ref. The theoretical study carried out by Fernández, Uggerud and Frenking [71] actually confirmed that the X 2 Me 7 + (X = Ge, Sn, Pb) ions also present a D 3h structure with a planar CH 3 group symmetrically bonded to two XMe 3 moieties. Hence, very likely, systems in which the SiMe 3 nucleophile is replaced by other electropositive groups, XMe 3 (X = Ge, Sn and Pb), will yield also X 2 Me 7 + stable species.…”
Section: Pentacovalent Carbon Atomsmentioning
confidence: 81%
“…As the central C atom (CH þ 3 cation) has only three valence electrons, shared with the H atoms, the C and the two Si atoms must form a two-electron, three-center bond (Dá valos et al, 2007). Theoretical works (Jemmis et al, 1979;Ferná ndez et al, 2007) have shown the stability of penta-coordinated carbenium ions and other cations containing more electropositive elements than carbon (Be and Group 13 and 14 elements) and whose bonding scheme also fits to a (2e, 3c) bond.…”
Section: Siðch 3 þ þmentioning
confidence: 99%